Analysis of the investments influence in environmental protection measures on the structure of ecological costs distribution on the example of the Republic of Sakha (Yakutia) - O. A. Bykanova (Вестник университета)
Modern investment processes can be considered the main factor in the development of individual constituent entities of the Russian Federation. The emergence of additional jobs, the improvement of social infrastructure contribute to the growth of the quality of life of the population. However, the active use of natural resources as a raw material base for industry and agriculture has consequences: the depletion of resources and the violation of their structure and quality. Environmental protection measures are an important component of the development of regions. The article сonsiders investments aimed at protecting land and water resources in the Republic of Sakha (Yakutia). The study of the statistics of costs for the conservation and restoration of water and land using the Gatev integral index allowed us to conclude about significant changes in current costs structure. Based on the correlation and regression analysis, the ratio between the Gatev index of structural differences in costs and the share of investments in the rehabilitation of soil and water resources with a correlation of 0.85 has been obtained. It has been concluded that a decrease in the level of attracted investments entails, in aggregate, a significant redistribution of funds for measures aimed at improving the natural resources of agricultural purposes.